Limits of interference of survival tourism in natural areas with various protective regimes - Płoskonka, Przemysław; Adamski, Paweł; Ciapała, Szymon (Studia Ecologiae et Bioethicae, 2018)
Survival as a form of tourism and recreation requires access to natural resources, including those with a high degree of naturalness. Due to their natural values and environmental functions, these areas are subject to various protection regimes. The article analyzes existing law regulations and assesses the impact of individual types of survival classes on natural areas. The conclusion states that law regulations are an important factor conditioning the possibility of practicing survivals in Poland, undertaking this form of activity must take place in close cooperation with the owners and managers of the areas, and the degree of interference in the natural environment depends on the subject of the classes and their duration.